Aluminum-coated aluminum nitride ceramic substrate for packaging and preparation method thereof

By forming a copper layer and a copper diamond layer on an aluminum-coated aluminum nitride ceramic substrate and plating nickel, the problems of warping and stress accumulation of the substrate under high temperature conditions are solved, and its thermal conductivity and thermal cycling reliability are improved.

CN119640266AActive Publication Date: 2025-03-18JIANGSU FERROTEC SEMICON TECH CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411730999.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-18
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

In the prior art, aluminum-covered ceramic substrates are prone to warping and stress accumulation due to temperature changes under high voltage, high current, high power density and strong heat dissipation conditions, resulting in device failure.

Method used

By forming a copper layer and a copper diamond layer on the thin and thick aluminum surfaces of the double-sided aluminum aluminum nitride ceramic sheets, and plating a nickel layer on the surface, using cold spraying process and diffusion sintering welding technology, an aluminum aluminum nitride ceramic substrate with high thermal conductivity and low expansion is prepared.

Benefits of technology

The thermal conductivity of the aluminum-covered aluminum nitride ceramic substrate is significantly improved, the thermal warping and stress accumulation problems caused by thermal cycling are reduced, and the thermal cycling reliability of the substrate is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640266A_ABST
    Figure CN119640266A_ABST
Patent Text Reader

Abstract

The invention discloses an aluminum-coated aluminum nitride ceramic substrate for packaging and a preparation method thereof, and relates to the technical field of semiconductors. An alloy coating is formed on the thin aluminum surface of the double-sided aluminum-coated aluminum nitride ceramic chip through a cold spraying process, and then a copper layer is diffused, sintered and welded for later use; performing niobium film sputtering and chemical copper plating on the diamond powder through magnetron sputtering and chemical copper plating processes to obtain copper-plated diamond, and performing cold spraying on the copper-plated diamond on the thick aluminum surface of the double-sided aluminum-coated aluminum nitride ceramic chip through cold spraying process treatment to obtain a copper diamond layer; and sequentially carrying out pretreatment activation and surface nickel plating on the double-sided aluminum-coated aluminum nitride ceramic chip to obtain the final aluminum-coated aluminum nitride ceramic substrate. The finished product obtained by the invention has good thermal conductivity, effectively reduces thermal resistance, and has good thermal cycle reliability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of semiconductor technology, in particular to an aluminum-coated aluminum nitride ceramic substrate for packaging and a preparation method thereof. Background Art

[0002] With the rapid development of IGBT power electronic devices in China, the technology of power electronic devices is developing rapidly towards high voltage, high current, high power density, strong heat dissipation, etc. As the packaging substrate of IGBT, aluminum nitride ceramic substrate with aluminum coating has excellent thermal conductivity, good thermal shock fatigue resistance, outstanding thermal stability, light structure and good aluminum wire bonding ability.

[0003] As the voltage and current range of power devices becomes larger and larger, the probability of device failure becomes larger and larger. The main reason is that the power dissipation per unit area is increasing, resulting in an increase in heat generation. The heat cannot be dissipated in time, causing device failure. In this process, the warping of the aluminum-coated ceramic substrate caused by temperature changes leads to internal stress accumulation. When these stresses exceed the fracture strength of the material, fracture will occur, causing device failure. Therefore, it is of great significance to study an aluminum-coated aluminum nitride ceramic substrate for packaging and its preparation method.

[0004] In order to overcome the defects of the prior art, the present invention provides an aluminum-coated aluminum nitride ceramic substrate for packaging and a preparation method thereof. Summary of the invention

[0005] The object of the present invention is to provide an aluminum-coated aluminum nitride ceramic substrate for packaging and a preparation method thereof, so as to solve the problems raised in the prior art.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A aluminum-clad aluminum nitride ceramic substrate for packaging, comprising a double-sided aluminum-clad aluminum nitride ceramic sheet, wherein the thin aluminum surface of the double-sided aluminum-clad aluminum nitride ceramic sheet is provided with a copper layer, and the surface of the copper layer is plated with a nickel layer; the thick aluminum surface of the double-sided aluminum-clad aluminum nitride ceramic sheet is provided with a copper diamond layer, and the surface of the copper diamond layer is plated with a nickel layer; wherein the thickness of the thin aluminum layer of the double-sided aluminum-clad aluminum nitride ceramic sheet is 0.1-0.4mm, and the thickness of the thick aluminum layer is 0.4-0.8mm; the thickness of the copper layer is 0.2-0.8mm; and the thickness of the copper diamond layer is 90-100μm.

[0008] A method for preparing an aluminum-coated aluminum nitride ceramic substrate for packaging, comprising the following steps:

[0009] Step 1: Weld the copper sheet onto the thin aluminum surface of the double-sided aluminum nitride ceramic sheet by diffusion sintering and set aside;

[0010] Step 2: Pre-treating the diamond micropowder and then copper-plating it to obtain copper-plated diamond micropowder;

[0011] Step 3: Take the copper-plated diamond powder obtained in step 2, and obtain a copper diamond layer on the thick aluminum surface of the double-sided aluminum-coated aluminum nitride ceramic sheet obtained in step 1 through a cold spraying process, and then perform pretreatment activation and surface nickel plating on the double-sided aluminum-coated aluminum nitride ceramic sheet in sequence to obtain the final aluminum-coated aluminum nitride ceramic substrate.

[0012] Preferably, the process parameters of diffusion sintering in step 1 are: temperature of 500° C., pressure of 3 MPa, vacuum degree of 0.01-0.5 Pa, heat preservation time of 30 min, and heating rate of 10° C. / min.

[0013] Preferably, the particle size of the diamond powder in step 2 is 10-15 μm; the pretreatment process is boiling in a degreasing solution for 5 minutes, boiling in a roughening solution for 30 minutes, ultrasonically oscillating in a sensitizing solution for 30 minutes, heating to 70°C in an activation solution for 30 minutes, and soaking in a degumming solution for 15 minutes. After each step is completed, it is washed with pure water until neutral.

[0014] Preferably, the copper plating in step 2 is carried out by chemical plating, and the composition of the chemical copper plating solution is: 10-40g / L CuSO4·5H2O, 20-60g / L Na2·EDTA, 4-8g / L NaOH, 20-40mL / L NH3·H2O; during chemical copper plating, the temperature is 50-55°C and the time is 15-20min; the thickness of the copper plating layer on the diamond surface is 1-3μm.

[0015] Preferably, the cold spraying process parameters in step 3 are: nozzle diameter of 0.5-1.5 mm, spray gun air pressure of 0.7-1 MPa, gas flow rate of 100-400 L / min, powder air flow velocity of 300-600 m / s, and powder feeding amount of 5-20 g / min.

[0016] Preferably, in step 3, the surface nickel plating adopts sodium hypophosphite system chemical nickel plating; the components of the sodium hypophosphite system are: 25-30g / L NiSO4·7H2O, 25-30g / L NaH2PO2·H2O, 15-20g / L CH3COONa, 10-20g / LNa3C6H5O·2H2O; when the surface nickel is plated, the temperature is 78-85°C, the time is 20-25min, and the stirring method is air stirring.

[0017] Preferably, in step 1, the double-sided aluminum nitride ceramic sheet is pretreated, and after ultrasonic cleaning of surface impurities with acetone and sandblasting roughening, a layer of alloy powder is cold-sprayed on the thin aluminum surface of the double-sided aluminum nitride ceramic sheet, and then the copper sheet is welded; wherein the content of each element in the alloy powder is: by mass percentage, 2.00-4.00% Cu, 0.20-0.40% Mg, 18.00-24.00% Si, 0.20-0.40% Fe, 0.1-0.3% Sc and the balance is Al; the cold spraying process parameters are: nozzle diameter is 0.5-1.5mm, spray gun air pressure is 0.7-0.8MPa, spraying distance is 10-20mm, gas temperature is 500-600℃, and powder feeding amount is 15-20g / min.

[0018] Preferably, after the diamond powder is pretreated in step 2, a W or Nb film is plated by magnetron sputtering, and then copper is plated; wherein the power of the magnetron sputtering is 100-200W, the applied bias voltage is -60V; and the coating thickness is 200-300nm.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The invention is characterized in that an alloy coating is formed on the thin aluminum surface of the double-sided aluminum-coated aluminum nitride ceramic sheet by a cold spraying process, and then a copper layer is welded by diffusion sintering for standby use; a niobium film is sputtered on diamond powder and chemically copper is plated by magnetron sputtering and chemical copper plating to obtain copper-plated diamond, and then a copper diamond layer is cold sprayed on the thick aluminum surface of the double-sided aluminum-coated aluminum nitride ceramic sheet by a cold spraying process; and then the double-sided aluminum-coated aluminum nitride ceramic sheet is pre-treated, activated and nickel-plated on the surface to obtain an aluminum-coated aluminum nitride ceramic substrate with a surface plating-copper-thin aluminum-aluminum nitride ceramic sheet-thick aluminum-copper diamond-surface plating structure; and the parameters of each step in the preparation process are complete, the layer thickness is strictly controlled, and the quality of the product is guaranteed.

[0021] A layer of alloy powder is cold-sprayed on the surface of the double-sided aluminum-coated aluminum nitride ceramic sheet, and then the copper layer is welded. On the one hand, the cold-sprayed alloy powder greatly improves the bonding strength between the copper layer and the aluminum layer, thereby increasing the product yield; on the other hand, the alloy has good thermal conductivity and low expansion properties, thereby reducing the risk of damage to the aluminum-coated aluminum nitride ceramic substrate caused by temperature changes; after sputtering a niobium film on the surface of the diamond micropowder, chemical copper plating is performed, and the niobium film improves the interface bonding strength between copper and diamond, while also increasing the thermal conductivity of copper diamond, thereby further increasing the thermal conductivity of the aluminum-coated ceramic substrate.

[0022] The finished product prepared by the present invention greatly improves the thermal conductivity of the aluminum-coated aluminum nitride ceramic substrate, reduces the thermal warping and stress accumulation problems caused by thermal cycling, and improves the thermal cycling reliability of the aluminum-coated aluminum nitride ceramic substrate. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a flow chart of the preparation method of Example 1 of the present invention;

[0024] Figure 2 This is a schematic diagram of the finished product structure of Example 1 of the present invention. DETAILED DESCRIPTION

[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] In the experiment, the double-sided aluminum nitride ceramic wafer was sourced from Jiangsu Fulehua Semiconductor Technology Co., Ltd.;

[0027] The particle size of diamond micro powder is 10-15 μm, purchased from Henan Huanghe Cyclone Co., Ltd.

[0028] The degreasing solution is a 10% sodium hydroxide solution; the roughening solution is a 15% nitric acid solution; the sensitizing solution is a mixed solution of 20g / L tin chloride and 30ml / L 36% hydrochloric acid; the activation solution is a 2g / L silver nitrate solution; the degumming solution is a 40g / L sodium hypophosphite solution;

[0029] The micro-etching solution contains 80 g / L sodium persulfate and 5% sulfuric acid; the pickling solution contains 6% sulfuric acid; and the activation solution contains 20 mL / L sulfuric acid and 15 mg / L palladium ions.

[0030] Embodiment 1:

[0031] Step 1: Select a double-sided aluminum nitride ceramic sheet with a specification of 139×190mm, a thin aluminum surface thickness of 0.3mm, and a thick aluminum surface thickness of 0.6mm, and a copper sheet with a specification of 139×190×0.4mm, and weld the copper sheet to the thin aluminum surface of the double-sided aluminum nitride ceramic sheet by diffusion sintering. The diffusion sintering process parameters are: temperature 500℃, pressure 3MPa, vacuum degree 0.4Pa, insulation 0.5h, heating rate 10℃ / min, and set aside;

[0032] Step 2: Pre-treat the diamond powder by boiling it in a degreasing solution for 5 minutes, boiling it in a roughening solution for 30 minutes, ultrasonically oscillating it in a sensitizing solution for 30 minutes, heating it to 70°C in an activation solution for 30 minutes, and soaking it in a degumming solution for 15 minutes. After each step, wash it with pure water until it is neutral. After the pre-treatment, chemical copper plating is performed for 18 minutes. The chemical copper plating solution has the following components: 20g / L CuSO4·5H2O, 40g / LNa2·EDTA, 6gNaOH, 30ml / LNH3·H2O, and the temperature of the chemical copper plating solution is 55°C. The thickness of the copper plating layer is 2.3μm, and copper-plated diamond powder is obtained.

[0033] Step 3: Take the copper-plated diamond powder obtained in step 2, and obtain a copper diamond layer with a thickness of 90 μm on the thick aluminum surface of the double-sided aluminum-coated aluminum nitride ceramic sheet in step 1 through a cold spray process, and then perform pretreatment activation, and sequentially perform microetching in a micro-etching solution for 100 seconds, pickling in a pickling solution for 90 seconds, and activation in an activation solution for 150 seconds. After each step is completed, wash with pure water. After the pretreatment activation is completed, the surface is nickel-plated, and a sodium hypophosphite system is used for chemical nickel plating. The sodium hypophosphite system composition is: 26g / LNiSO4·7H2O, 27g / LNaH2PO2·H2O, 17g / L CH3COONa, 15g / LNa3C6H5O·2H2O; when the surface is nickel-plated, the temperature is 83°C, the time is 22min, and air stirring is performed to obtain an aluminum-coated aluminum nitride ceramic substrate.

[0034] The cold spraying process parameters are as follows: nozzle diameter is 1.2 mm, spray gun air pressure is 0.8 MPa, gas flow rate is 230 L / min, powder air flow velocity is 450 m / s, and powder feeding amount is 12 g / min; after cold spraying, the roughness Ra of the ceramic piece is 1.0 μm.

[0035] Embodiment 2:

[0036] Step 1: Select a double-sided aluminum nitride ceramic sheet with a specification of 139×190mm, a thin aluminum surface thickness of 0.2mm, and a thick aluminum surface thickness of 0.7mm, and a copper sheet with a specification of 139×190×0.6mm, and weld the copper sheet to the thin aluminum surface of the double-sided aluminum nitride ceramic sheet by diffusion sintering. The diffusion sintering process parameters are: temperature 500℃, pressure 3MPa, vacuum degree 0.5Pa, insulation 0.5h, heating rate 10℃ / min, and set aside;

[0037] Step 2: Pre-treat the diamond powder by boiling it in a degreasing solution for 5 minutes, boiling it in a roughening solution for 30 minutes, ultrasonically oscillating it in a sensitizing solution for 30 minutes, heating it to 70°C in an activation solution for 30 minutes, and soaking it in a degumming solution for 15 minutes. After each step, wash it with pure water until it is neutral. After the pre-treatment, chemical copper plating is performed for 20 minutes. The chemical copper plating solution has the following components: 22g / L CuSO4·5H2O, 50g / LNa2·EDTA, 6gNaOH, 40ml / LNH3·H2O, and the temperature of the chemical copper plating solution is 55°C. The thickness of the copper plating layer is 2.5μm, and copper-plated diamond powder is obtained.

[0038] Step 3: Take the copper-plated diamond powder obtained in step 2, and obtain a copper diamond layer with a thickness of 100 μm on the thick aluminum surface of the double-sided aluminum nitride ceramic sheet coated with aluminum in step 1 through a cold spray process, and then after pretreatment and activation, the double-sided aluminum nitride ceramic sheet is sequentially micro-etched in a micro-etching solution for 100 seconds, pickled in a pickling solution for 90 seconds, and activated in an activation solution for 150 seconds. After each step is completed, it is washed with pure water. After the pretreatment and activation, the surface is nickel-plated, and a sodium hypophosphite system is used for chemical nickel plating. The sodium hypophosphite system composition is: 25g / LNiSO4·7H2O, 25g / LNaH2PO2·H2O, 15g / L CH3COONa, 10g / LNa3C6H5O·2H2O; when the surface is nickel-plated, the temperature is 82°C, the time is 25min, and air stirring is performed to obtain an aluminum-coated aluminum nitride ceramic substrate.

[0039] The cold spraying process parameters are as follows: nozzle diameter is 1.0 mm, spray gun air pressure is 0.9 MPa, gas flow rate is 200 L / min, powder air flow velocity is 400 m / s, and powder feeding amount is 14 g / min; after cold spraying, the roughness Ra of the ceramic piece is 1.2 μm.

[0040] Example 3: Referring to Example 1, pretreatment of the double-sided aluminum nitride ceramic sheet is added, and the specific steps are as follows:

[0041] Step 1: Select a double-sided aluminum nitride ceramic sheet with a specification of 139×190mm, a thin aluminum surface thickness of 0.3mm, and a thick aluminum surface thickness of 0.6mm, and a copper sheet with a specification of 139×190×0.4mm, pre-treat the double-sided aluminum nitride ceramic sheet, clean the surface impurities with acetone ultrasonically and roughen it with sandblasting, cold spray a layer of alloy powder on the thin aluminum surface of the double-sided aluminum nitride ceramic sheet, and then weld the copper sheet to the thin aluminum surface of the double-sided aluminum nitride ceramic sheet by diffusion sintering, and the diffusion sintering process parameters are: temperature 500℃, pressure 3MPa, vacuum degree 0.4Pa, insulation 0.5h, heating rate 10℃ / min, and set aside;

[0042] Step 2: Pre-treat the diamond powder by boiling it in a degreasing solution for 5 minutes, boiling it in a roughening solution for 30 minutes, ultrasonically oscillating it in a sensitizing solution for 30 minutes, heating it to 70°C in an activation solution for 30 minutes, and soaking it in a degumming solution for 15 minutes. After each step, wash it with pure water until it is neutral. After the pre-treatment, chemical copper plating is performed for 18 minutes. The chemical copper plating solution has the following components: 20g / L CuSO4·5H2O, 40g / LNa2·EDTA, 6gNaOH, 30ml / LNH3·H2O, and the temperature of the chemical copper plating solution is 55°C. The thickness of the copper plating layer is 2.3μm, and copper-plated diamond powder is obtained.

[0043] Step 3: Take the copper-plated diamond powder obtained in step 2, and obtain a copper diamond layer with a thickness of 90 μm on the thick aluminum surface of the double-sided aluminum nitride ceramic sheet coated with aluminum in step 1 through a cold spray process, and then pre-treat and activate the double-sided aluminum nitride ceramic sheet, and sequentially micro-etch the double-sided aluminum nitride ceramic sheet in a micro-etching solution for 100 seconds, pickle in a pickling solution for 90 seconds, and activate in an activation solution for 150 seconds. After each step is completed, wash with pure water, and nickel-plate the surface after the pre-treatment and activation. Chemical nickel plating is performed using a sodium hypophosphite system, and the components of the sodium hypophosphite system are: 26 g / LNiSO4·7H2O, 27 g / LNaH2PO2·H2O, 17 g / L CH3COONa, and 15 g / LNa3C6H5O·2H2O; when nickel-plating the surface, the temperature is 83°C, the time is 22 minutes, and air stirring is performed to obtain an aluminum-coated aluminum nitride ceramic substrate.

[0044] The contents of each element in the alloy powder in step 1 are: 4.00% Cu, 0.35% Mg, 20.05% Si, 0.30% Fe, 0.2% Sc and the balance Al, by mass percentage; the cold spraying process parameters are: nozzle diameter of 1.2 mm, spray gun air pressure of 0.8 MPa, spraying distance of 20 mm, gas temperature of 550°C, and powder feeding rate of 15 g / min.

[0045] The cold spraying process parameters in step 3 are: nozzle diameter is 1.2 mm, spray gun air pressure is 0.8 MPa, gas flow rate is 230 L / min, powder gas flow velocity is 450 m / s, and powder feeding amount is 12 g / min; after cold spraying, the roughness Ra of the ceramic piece is 1.0 μm.

[0046] Example 4: Referring to Example 1, a Nb film is added to the diamond powder by magnetron sputtering, and the specific steps are as follows:

[0047] Step 1: Select a double-sided aluminum nitride ceramic sheet with a specification of 139×190mm, a thin aluminum surface thickness of 0.3mm, and a thick aluminum surface thickness of 0.6mm, and a copper sheet with a specification of 139×190×0.4mm, and weld the copper sheet to the thin aluminum surface of the double-sided aluminum nitride ceramic sheet by diffusion sintering. The diffusion sintering process parameters are: temperature 500℃, pressure 3MPa, vacuum degree 0.4Pa, insulation 0.5h, heating rate 10℃ / min, and set aside;

[0048] Step 2: Pre-treat the diamond powder, boil it in a degreasing solution for 5 minutes, boil it in a roughening solution for 30 minutes, oscillate it in a sensitizing solution for 30 minutes, heat it to 70°C in an activation solution for 30 minutes, and soak it in a degumming solution for 15 minutes. After each step, wash it with pure water until it is neutral. After the pre-treatment, magnetron coating is performed. The power of magnetron sputtering is 125W, and a bias voltage of -60V is applied to obtain a Nb coating thickness of 300nm. Then, chemical copper plating is performed for 18 minutes. The chemical copper plating solution composition is: 20g / L CuSO4·5H2O, 40g / LNa2·EDTA, 6g NaOH, 30ml / LNH3·H2O, and the temperature of the chemical copper plating solution is 55°C; the thickness of the copper plating layer is 2.3μm, and copper-plated diamond powder is obtained;

[0049] Step 3: Take the copper-plated diamond powder obtained in step 2, and obtain a copper diamond layer with a thickness of 90 μm on the thick aluminum surface of the double-sided aluminum-coated aluminum nitride ceramic sheet in step 1 through a cold spray process, and then pre-treat and activate the double-sided aluminum-coated aluminum nitride ceramic sheet, in turn, micro-etching in a micro-etching solution for 100 seconds, pickling in a pickling solution for 90 seconds, and activating in an activation solution for 150 seconds. After each step is completed, wash with pure water. After the pre-treatment and activation, nickel is plated on the surface, and chemical nickel plating is performed using a sodium hypophosphite system. The components of the sodium hypophosphite system are: 26g / LNiSO4·7H2O, 27g / LNaH2PO2·H2O, 17g / L CH3COONa, and 15g / LNa3C6H5O·2H2O; when nickel is plated on the surface, the temperature is 83°C, the time is 22min, and air stirring is performed to obtain an aluminum-coated aluminum nitride ceramic substrate.

[0050] The cold spraying process parameters are as follows: nozzle diameter is 1.2 mm, spray gun air pressure is 0.8 MPa, gas flow rate is 230 L / min, powder air flow velocity is 450 m / s, and powder feeding amount is 12 g / min; after cold spraying, the roughness Ra of the ceramic piece is 1.0 μm.

[0051] Example 5: Referring to Example 4, pretreatment of the aluminum nitride ceramic sheet is added, and the specific steps are as follows:

[0052] Step 1: Select a double-sided aluminum nitride ceramic sheet with a specification of 139×190mm, a thin aluminum surface thickness of 0.3mm, and a thick aluminum surface thickness of 0.6mm, and a copper sheet with a specification of 139×190×0.4mm, pre-treat the double-sided aluminum nitride ceramic sheet, clean the surface impurities with acetone ultrasonically and roughen it with sandblasting, cold spray a layer of alloy powder on the thin aluminum surface, and then weld the copper sheet to the thin aluminum surface of the double-sided aluminum nitride ceramic sheet by diffusion sintering. The diffusion sintering process parameters are: temperature 500℃, pressure 3MPa, vacuum degree 0.4Pa, insulation 0.5h, heating rate 10℃ / min, and set aside;

[0053] Step 2: Pre-treat the diamond powder, boil it in a degreasing solution for 5 minutes, boil it in a roughening solution for 30 minutes, oscillate it in a sensitizing solution for 30 minutes, heat it to 70°C in an activation solution for 30 minutes, and soak it in a degumming solution for 15 minutes. After each step, wash it with pure water until it is neutral. After the pre-treatment, magnetron coating is performed. The power of magnetron sputtering is 125W, and a bias voltage of -60V is applied to obtain a Nb coating thickness of 300nm. Then, chemical copper plating is performed for 18 minutes. The chemical copper plating solution composition is: 20g / L CuSO4·5H2O, 40g / LNa2·EDTA, 6g NaOH, 30ml / LNH3·H2O, and the temperature of the chemical copper plating solution is 55°C; the thickness of the copper plating layer is 2.3μm, and copper-plated diamond powder is obtained;

[0054] Step 3: Take the copper-plated diamond powder obtained in step 2, and obtain a copper diamond layer with a thickness of 90 μm on the thick aluminum surface of the double-sided aluminum-coated aluminum nitride ceramic sheet in step 1 through a cold spray process, and then pre-treat and activate the double-sided aluminum-coated aluminum nitride ceramic sheet, in turn, micro-etching in a micro-etching solution for 100 seconds, pickling in a pickling solution for 90 seconds, and activating in an activation solution for 150 seconds. After each step is completed, wash with pure water. After the pre-treatment and activation, nickel is plated on the surface, and chemical nickel plating is performed using a sodium hypophosphite system. The components of the sodium hypophosphite system are: 26g / LNiSO4·7H2O, 27g / LNaH2PO2·H2O, 17g / L CH3COONa, and 15g / LNa3C6H5O·2H2O; when nickel is plated on the surface, the temperature is 83°C, the time is 22min, and air stirring is performed to obtain an aluminum-coated aluminum nitride ceramic substrate.

[0055] The contents of each element in the alloy powder in step 1 are: 4.00% Cu, 0.35% Mg, 20.05% Si, 0.30% Fe, 0.2% Sc and the balance Al, by mass percentage; the cold spraying process parameters are: nozzle diameter of 1.2 mm, spray gun air pressure of 0.8 MPa, spraying distance of 20 mm, gas temperature of 550°C, and powder feeding rate of 15 g / min.

[0056] The cold spraying process parameters in step 3 are: nozzle diameter is 1.2 mm, spray gun air pressure is 0.8 MPa, gas flow rate is 230 L / min, powder gas flow velocity is 450 m / s, and powder feeding amount is 12 g / min; after cold spraying, the roughness Ra of the ceramic piece is 1.0 μm.

[0057] Comparative Example 1: Referring to Example 1, the difference therefrom is that the copper diamond layer is removed, and the specific steps are as follows:

[0058] Step 1: Select a double-sided aluminum-clad aluminum nitride ceramic sheet with a specification of 139×190mm, a thin aluminum surface thickness of 0.3mm, and a thick aluminum surface thickness of 0.6mm, and a copper sheet with a specification of 139×190×0.4mm, and weld the copper sheet to the thin aluminum surface of the double-sided aluminum-clad aluminum nitride ceramic sheet by diffusion sintering. The diffusion sintering process parameters are: temperature 500°C, pressure 3MPa, vacuum degree 0.4Pa, insulation 0.5h, and heating rate 10°C / min; forming a copper-aluminum-aluminum nitride ceramic sheet-aluminum structure;

[0059] Step 2: Take the double-sided aluminum-coated aluminum nitride ceramic wafer in step 1 for pretreatment activation, and sequentially perform microetching in a microetching solution for 100 seconds, pickling in a pickling solution for 90 seconds, and activation in an activation solution for 150 seconds. After each step is completed, wash with pure water. After the pretreatment activation is completed, perform surface nickel plating, using a sodium hypophosphite system for chemical nickel plating, and the sodium hypophosphite system composition is: 26g / LNiSO4·7H2O, 27g / LNaH2PO2·H2O, 17g / L CH3COONa, 15g / LNa3C6H5O·2H2O; when the surface is nickel-plated, the temperature is 83°C, the time is 22min, and air stirring is performed to obtain an aluminum-coated aluminum nitride ceramic substrate.

[0060] Comparative Example 2: Referring to Example 5, the difference therefrom is that the copper diamond layer is removed, and the specific steps are as follows:

[0061] Step 1: Select a double-sided aluminum nitride ceramic sheet with a specification of 139×190mm, a thin aluminum surface thickness of 0.3mm, and a thick aluminum surface thickness of 0.6mm, and a copper sheet with a specification of 139×190×0.4mm, pre-treat the double-sided aluminum nitride ceramic sheet, clean the surface impurities with acetone ultrasonically and roughen it with sandblasting, cold spray a layer of alloy powder on the thin aluminum surface, and then weld the copper sheet to the thin aluminum surface of the double-sided aluminum nitride ceramic sheet by diffusion sintering. The diffusion sintering process parameters are: temperature 500℃, pressure 3MPa, vacuum degree 0.4Pa, insulation 0.5h, heating rate 10℃ / min, and set aside;

[0062] Step 2: Take the double-sided aluminum-coated aluminum nitride ceramic sheet in step 1 for pretreatment and activation, micro-etching for 100s, pickling for 90s, and activation for 150s in sequence, and wash with pure water after each step is completed. After the pretreatment and activation, the surface is nickel-plated using a sodium hypophosphite system for chemical nickel plating. The components of the sodium hypophosphite system are: 26g / LNiSO4·7H2O, 27g / LNaH2PO2·H2O, 17g / LCH3COONa, 15g / LNa3C6H5O·2H2O; when the surface is nickel-plated, the temperature is 83°C, the time is 22min, and air stirring is performed to obtain an aluminum-coated aluminum nitride ceramic substrate.

[0063] The contents of each element in the alloy powder in step 1 are: 4.00% Cu, 0.35% Mg, 20.05% Si, 0.30% Fe, 0.2% Sc and the balance Al, by mass percentage; the cold spraying process parameters are: nozzle diameter of 1.2 mm, spray gun air pressure of 0.8 MPa, spraying distance of 20 mm, gas temperature of 550°C, and powder feeding rate of 15 g / min.

[0064] Detection test:

[0065] Hot and cold cycle performance test: The aluminum-clad aluminum nitride ceramic substrates prepared in Examples 1-5 and Comparative Examples 1-2 were used as samples and zinc-immersion hot and cold cycle tests were performed in a TSE-12-A high and low temperature cycle test chamber. Parameter settings: Cycle temperature: -40°C to 125°C, test standard: GB / T 2423.22-2012 Environmental testing Part 2: Test method Test N: Temperature change. Each sample was cycled 500 times. The warpage value of the copper-clad surface of the sample was detected before and after the cycle, and the test temperature was room temperature.

[0066] Before hot and cold cycle After hot and cold cycle Example 1 -142μm -60μm Example 2 -152μm -86μm Example 3 -132μm -85μm Example 4 -139μm -88μm Example 5 -129μm -90μm Comparative Example 1 -122μm 53μm Comparative Example 2 -134μm 36μm

[0067] Conclusion: According to the warpage value data before and after the hot and cold cycle test of the embodiments and comparative examples, it is concluded that by adding a copper diamond layer, the thermal conductivity of the aluminum-coated ceramic substrate can be significantly improved and the warpage can be improved; by comparing Example 1 with Examples 3-4, cold spraying alloy powder and sputtering a Nb layer on the diamond surface are beneficial to improving the thermal conductivity of the aluminum-coated aluminum nitride ceramics. By comparing Example 1 with Example 5, the aluminum-coated aluminum nitride substrate prepared by cold spraying alloy powder and sputtering a Nb layer on the diamond surface has obvious improvement in warpage.

[0068] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. An aluminum-coated aluminum nitride ceramic substrate for packaging, characterized in that: It comprises a double-sided aluminum nitride ceramic sheet, wherein the thin aluminum surface of the double-sided aluminum nitride ceramic sheet is provided with a copper layer, and the surface of the copper layer is plated with a nickel layer; the thick aluminum surface of the double-sided aluminum nitride ceramic sheet is provided with a copper diamond layer, and the surface of the copper diamond layer is plated with a nickel layer; wherein the thickness of the thin aluminum layer of the double-sided aluminum nitride ceramic sheet is 0.1-0.4mm, and the thickness of the thick aluminum layer is 0.4-0.8mm; the thickness of the copper layer is 0.2-0.8mm; and the thickness of the copper diamond layer is 90-100μm.

2. A method for preparing an aluminum-coated aluminum nitride ceramic substrate for packaging, characterized in that: The following steps are involved: Step 1: Weld the copper sheet onto the thin aluminum surface of the double-sided aluminum nitride ceramic sheet by diffusion sintering and set aside; Step 2: Pre-treating the diamond micropowder and then copper-plating it to obtain copper-plated diamond micropowder; Step 3: Take the copper-plated diamond powder obtained in step 2, and obtain a copper diamond layer on the thick aluminum surface of the double-sided aluminum-coated aluminum nitride ceramic sheet obtained in step 1 through a cold spraying process, and then perform pretreatment activation and surface nickel plating on the double-sided aluminum-coated aluminum nitride ceramic sheet in sequence to obtain the final aluminum-coated aluminum nitride ceramic substrate.

3. The method for preparing an aluminum-coated aluminum nitride ceramic substrate for packaging according to claim 2, characterized in that: The process parameters of diffusion sintering in step 1 are: temperature of 500°C, pressure of 3MPa, vacuum degree of 0.01-0.5Pa, heat preservation for 30min, and heating rate of 10°C / min.

4. The method for preparing an aluminum-coated aluminum nitride ceramic substrate for packaging according to claim 2, characterized in that: The particle size of the diamond powder in step 2 is 10-15 μm; the pretreatment process is boiling in a degreasing solution for 5 minutes, boiling in a roughening solution for 30 minutes, ultrasonic oscillation in a sensitizing solution for 30 minutes, heating to 70° C. in an activation solution for 30 minutes, and soaking in a degumming solution for 15 minutes. After each step is completed, it is washed with pure water until neutral.

5. The method for preparing an aluminum-coated aluminum nitride ceramic substrate for packaging according to claim 2, characterized in that: In step 2, the copper plating is carried out by chemical plating, and the chemical copper plating solution comprises: 10-40 g / L CuSO4·5H2O, 20-60 g / L Na2·EDTA, 4-8 g / L NaOH, 20-40 mL / L NH3·H2O; the chemical copper plating temperature is 50-55° C., and the time is 15-20 min; and the thickness of the copper plating layer on the diamond surface is 1-3 μm.

6. The method for preparing an aluminum-coated aluminum nitride ceramic substrate for packaging according to claim 2, characterized in that: The cold spraying process parameters in step 3 are: nozzle diameter 0.5-1.5 mm, spray gun air pressure 0.7-1 MPa, gas flow rate 100-400 L / min, powder air flow velocity 300-600 m / s, and powder feeding amount 5-20 g / min.

7. The method for preparing an aluminum-coated aluminum nitride ceramic substrate for packaging according to claim 2, characterized in that: In step 3, the surface nickel plating adopts sodium hypophosphite system chemical nickel plating; the components of the sodium hypophosphite system are: 25-30g / LNiSO4·7H2O, 25-30g / L NaH2PO2·H2O, 15-20g / L CH3COONa, 10-20g / L Na3C6H5O·2H2O; when the surface nickel is plated, the temperature is 78-85°C, the time is 20-25min, and the stirring method is air stirring.

8. The method for preparing an aluminum-coated aluminum nitride ceramic substrate for packaging according to claim 2, characterized in that: The thin aluminum surface of the double-sided aluminum nitride ceramic sheet in step 1 is pretreated, and after surface impurities are ultrasonically cleaned with acetone and roughened by sandblasting, a layer of alloy powder is cold-sprayed on the thin aluminum surface of the double-sided aluminum nitride ceramic sheet, and then the copper sheet is welded; wherein the content of each element in the alloy powder is: by mass percentage, 2.00-4.00% Cu, 0.20-0.40% Mg, 18.00-24.00% Si, 0.20-0.40% Fe, 0.1-0.3% Sc and the balance is Al.

9. The method for preparing an aluminum-coated aluminum nitride ceramic substrate for packaging according to claim 8, characterized in that: The cold spraying process parameters are: nozzle diameter is 0.5-1.5mm, spray gun air pressure is 0.7-0.8MPa, spraying distance is 10-20mm, gas temperature is 500-600℃, and powder feeding amount is 15-20g / min.

10. The method for preparing an aluminum-coated aluminum nitride ceramic substrate for packaging according to claim 2, characterized in that: In step 2, after the diamond powder is pretreated, a W or Nb film is plated by magnetron sputtering, and then copper is plated; the power of the magnetron sputtering is 100-200W, the bias voltage applied is -60V; the coating thickness is 200-300nm.

Citation Information

Patent Citations

  • Preparation method of aluminum-coated aluminum nitride ceramic substrate double-sided heat dissipation power module

    CN118098989A

  • Preparation method of aluminum-coated ceramic lining plate with low thermal expansion coefficient

    CN118835200A

  • Thermal structures for dissipating heat and methods for manufacture thereof

    US20200194334A1